TLR2 Expression in Relation to IL-6 and IL-1 β and their Natural Regulators Production by PMN and PBMC in Patients with Lyme Disease (Mediators of Inflammation)
Recently, it has been reported that TLR2 on macrophages plays a unique role in the inflammatory response and host defense to infection with <emph>Borrelia burgdorferi</emph> (<emph>Bb</emph>) which is an etiologic agent of Lyme disease. Experimental studies show that PMNs also play an essential role in infection control by <emph>Bb</emph>. However, there is no available data about TLR2 expression on PMN in the course of Lyme disease. In the present study, TLR2 expression and production of IL-1 β and IL-6 as well as their natural regulators (sIL-1RII, IL-1Ra and sIL-6R α , sgp130, resp) by PMN of peripheral blood in patients with Lyme disease were examined. For the purpose of comparison, the same activity of autologous peripheral blood mononuclear cells (PBMCs) was estimated. An effect of rhIL-15 on TLR2 and cytokine secretion was also studied. Increased TLR2 expression in unstimulated neutrophils suggests an important role of these cells in mechanism recognition of <emph>B burgdorferi</emph> in patients with Lyme disease. The relationship between IL-1 β and IL-6 as well as their regulators by unstimulated PMN and PBMC, observed in the present study, may lead to enhanced IL-6- and to inhibition of IL-1 β -mediated reactions in this patient group. Changes in the TLR2 expression after rhIL-15 stimulation appear to have a favorable effect on mechanism recognition of <emph>Bb</emph>. The relations between IL-6 and its regulators (sIL-6R α and sgp130) as well as between IL-1 β and its regulators (IL-1Ra and sIL-1RII) after rhIL-15 stimulation may lead to enhanced IL-1 β - and IL-6-mediated inflammatory reactions in the course of Lyme disease.